2009
DOI: 10.1002/bmc.1265
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of UPLC‐MS/MS method for simultaneous determination of gestodene and ethinyl estradiol in rat plasma

Abstract: A selective and sensitive ultra-performance liquid chromatography method with tandem mass spectrometric detection for simultaneous determination of gestodene (GES) and ethinyl estradiol (EE) in rat plasma was developed and validated. GES, EE and the internal standard, norgestrel, were extracted with ethyl acetate, derivatized (EE only) with dansyl chloride and then back-extracted into diethyl ether-hexane (2:1, v/v). The separation was performed on an ACQUITY UPLC BEH C(18) column with gradient elution using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…In a previous study, the metabolism of some compound had been reported by this multiple combination technique method [21,22], while there has been no fully integrated study of the metabolite of multiple components in CHMs. Metabolite identification has been greatly improved by the availability of modern mass spectrometers that are capable of providing high resolution (15,000 at full width at half maximum) and accurate mass (error < 5 ppm).…”
Section: Identification Of the Metabolites Of G Longituba Extract Inmentioning
confidence: 99%
“…In a previous study, the metabolism of some compound had been reported by this multiple combination technique method [21,22], while there has been no fully integrated study of the metabolite of multiple components in CHMs. Metabolite identification has been greatly improved by the availability of modern mass spectrometers that are capable of providing high resolution (15,000 at full width at half maximum) and accurate mass (error < 5 ppm).…”
Section: Identification Of the Metabolites Of G Longituba Extract Inmentioning
confidence: 99%
“…In the example of sildenafil, the choice of deuterated internal standard (sildenafild 3 ) enabled a good assay performance in spite of a high signal ion suppression (Witjes et al, 2010). Norgestrel was selected as an internal standard for gestodene/ethinyl estradiol assay because of its structural resemblance to the analytes and structural properties that included ionization potential and comparable extraction recovery (Xiong et al, 2010). Interestingly, Nirogi et al (2009) chose to use two internal standards, namely rosuvastatin and propranolol, for the determination of emtricitabine, efavirenz and tenofovir.…”
Section: Sir -mentioning
confidence: 99%
“…Shou, Jiang, and Weng (2004) described an LC-MS/MS method for the analysis of EE2 with dansyl chloride derivatization. EE in combination with norethindrone has been determined by HPLC-MS/MS in human plasma using a derivatization agent by Li et al (2010). A bioequivalence study of generic formulation having EE and chlormadinone acetate has been reported by Bonn, Urte, Martin, and Lucio (2009) in healthy female subjects.…”
Section: Introductionmentioning
confidence: 99%